2021
DOI: 10.3390/ijms22094762
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of microRNAs in Renin–Angiotensin-System-Induced Cardiac Remodelling

Abstract: Current knowledge on the renin–angiotensin system (RAS) indicates its central role in the pathogenesis of cardiovascular remodelling via both hemodynamic alterations and direct growth and the proliferation effects of angiotensin II or aldosterone resulting in the hypertrophy of cardiomyocytes, the proliferation of fibroblasts, and inflammatory immune cell activation. The noncoding regulatory microRNAs has recently emerged as a completely novel approach to the study of the RAS. A growing number of microRNAs ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 253 publications
(357 reference statements)
0
9
0
1
Order By: Relevance
“…In brief, angiotensinogen produced from the liver is converted into Ang I and Ang II via renin, esterase-2, cathepsin G, kallikrein, chymase, and angiotensin-converting enzyme. Ubiquitous actions of Ang II can be attributed to activation of several signal transduction pathways modulated by receptors including AT 1 R and AT 2 R to initiate RAS or further get cleaved into peptides namely, Ang IV, Ang (1–7), and alamandine, which express their effects via AT4 R, Mas R and MrgD, respectively ( Adamcova et al, 2021 ; Matsubara, 1998 ). Interestingly, administration of Ang (1–7) was evidenced to provide a protective effect during chronic infusion of Ang II in rats ( Grobe et al, 2007 ).…”
Section: Angiotensin II Receptors and Signaling Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, angiotensinogen produced from the liver is converted into Ang I and Ang II via renin, esterase-2, cathepsin G, kallikrein, chymase, and angiotensin-converting enzyme. Ubiquitous actions of Ang II can be attributed to activation of several signal transduction pathways modulated by receptors including AT 1 R and AT 2 R to initiate RAS or further get cleaved into peptides namely, Ang IV, Ang (1–7), and alamandine, which express their effects via AT4 R, Mas R and MrgD, respectively ( Adamcova et al, 2021 ; Matsubara, 1998 ). Interestingly, administration of Ang (1–7) was evidenced to provide a protective effect during chronic infusion of Ang II in rats ( Grobe et al, 2007 ).…”
Section: Angiotensin II Receptors and Signaling Pathwaysmentioning
confidence: 99%
“…miRNA including miR-154, miR-155, miR-132, miR-21, miR-503, miR-214, miR-19a, and miR-410 are involved in promoting hypertrophy, fibrosis, apoptosis, and inflammation. On other hand, miR-16, miR-98, miR-30a, miR-133, miR-433 possess cardio-protective effects ( Wang Q. et al, 2019 ; Song et al, 2019 ; Adamcova et al, 2021 ). Luciferase assay evidenced that miR-214 acts as a target for Long non-coding RNA (lncRNA) Plscr4 and ameliorated levels of miR-214 oppose the anti-hypertrophic effect of Plscr4 in Ang II treated cardiomyocytes via lncRNA Plscr4-miR-214-mitofusin (Mfn2) axis ( Lv et al, 2018 ).…”
Section: Angiotensin II In Cardiovascular Systemmentioning
confidence: 99%
“…It was reported that the loss of heart regenerative capacity was triggered by increasing thyroid hormones [ 13 ]. In addition, the analysis indicated that some m 6 A differential lncRNAs were also enriched in ‘insulin-like growth factor receptor’ and ‘response to angiotensin’, which are participating in cardiac hypertrophy [ 36 , 44 ]. m 6 A differential lncRNAs enriched in myocardial regeneration-related pathways, such as ‘TGF-beta signaling pathway’ is well documented [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, postpartum relative hyperoxia inhibited glycolysis leading to halt regenerative ability [40], while hypoxia-induced anaerobic metabolism elevated glycolysis to promote regenerative milieu within the myocardium [41][42][43]. Angiotensin was known to promote interstitial cardiac fibrosis and hypertrophy [44]. In contrast, lncRNAs with down-methylated sites were involved in 'Cardiac muscle contraction' and 'Cell cycle-yeast' (Fig.…”
Section: Gene Ontology and Kyoto Encyclopedia Of Genes And Genomes An...mentioning
confidence: 99%
“…Data from non-renal fibroblasts suggest additional profibrotic effects of hypoxia in renal fibroblasts in suppressing apoptosis, inducing the production of proinflammatory factors and upregulating components of the renin-angiotensin system [13,14]. However, this issue has not been studied in patients with NS.…”
Section: Discussion the Central Role Of Hypoxia In Renal Fibrosis Sug...mentioning
confidence: 99%